Effect of Habbatussauda (Nigella sativa) Extract on Rat Sperm Count (Rattus norvegicus) - Muhammad Ja’far Luthfi; Hikmah Supriyati; Sindi Farhana (Kaunia: Integration and Interconnection Islam and Science, 2016)
Sperm sample from epididimal source can be determined its motility using minimal amount of equipment. These methods will aid researcher and practitioner in sperm motility analysis to determined sperm quality rapidly and practically.